Impact of Open and Closed Kinetic Chain Exercises on Patellofemoral Pain Syndrome: A Study Performed at Al-Khums Teaching Hospital, Al-Khums City - Osama Aljahmi,; Mwlwd Almarymy,; Meftah Abulgasem,; Husam Belhaj,; Tawfiq Alhddad,; Ayiman Abdulqadir, (AlQalam Journal of Medical and Applied Sciences, 2025)
This research aimed to evaluate the efficacy of open kinetic chain (OKC) and closed kinetic chain (CKC) exercise regimens in the rehabilitation of individuals with Patellofemoral Pain Syndrome (PFPS). An exercise group for OKC patients and a group for CKC patients were each assigned 60 patients with PFPS randomly. Eight sessions were conducted over six weeks as an element of a rehabilitation program. The amount of discomfort was assessed using the Visual Analog Scale (VAS), the patient's functional status was evaluated using the Kujala Patellofemoral Score, and the strength and stability of the quadriceps muscles were determined by assessing muscle activity. We used SPSS software (version 26) to analyze the data, using paired t-tests for intra-group comparisons and independent t-tests for inter-group comparisons. A p-value of less than 0.05 was deemed as statistically significant. Both groups had significant improvements in job capacity, reduced discomfort, and enhanced leg strength after the intervention. The CKC group had superior performance in functional daily tasks, proprioception, and joint stability. While both CKC and OKC workouts may assist in managing PFPS, CKC exercises seem superior since they enhance joint stiffness and facilitate functional recovery.